Obesity and early reoperation rate after elective lumbar spine surgery: a population-based study - Gaudelli, Cinzia; Thomas, Ken (Evidence-Based Spine-Care Journal, 2012)
Study design: Population-based retrospective cohort study.Clinical question: Are patients with a body mass index (BMI) of 35 or more who undergo elective lumbar spine surgery at increased risk of post-surgical complications, as evidenced by reoperation within a 3-month period?Methods: The Alberta Health and Wellness Administrative database was queried to identify patients who underwent elective lumbar spine surgery over a 24-month period. This same database was used to classify subjects as obese (BMI ≥35) and non-obese (BMI <35) and to determine who underwent repeated surgical intervention. The rate of reoperation was determined for both the obese and non-obese groups; further analyses were performed to determine whether certain subjects were at increased risk of reoperation.Results: The point estimate for relative risk for requiring reoperation was 1.73 (95% confidence interval, 1.03–2.90) for obese subjects compared with non-obese subjects. The adjusted point estimate shows that deformity correction surgery is predictive for early reoperation while obesity is not.Conclusions: In obese subjects we observed an increased complication rate after elective lumbar spine surgery, as evidenced by reoperation rates within 3 months. When we considered other possible associations with reoperation, in adjusted analysis, deformity surgery was found to be predictive of early reoperation.The definiton of the different classes of evidence is available here.